Isolation of Natural Derivated Steroidal from Bark Stem of Melochia umbellata (Houtt) Stapf var. degrabrata K. - Usman, Usman; Soekamto, Nunuk Hariani; Natsir, Muhammad; Maulidiyah, Maulidiyah (Asian Journal of Chemistry, 2020)
Exploration of the natural product as pharmaceutical drug widely discover continuously for human life. The unique chemical compounds have been explored from bark stem of Melochia Umbellata (Houtt) Stapf var. degrabrata K. (M. umbellata) which is obtained from South Sulawesi, Indonesia. We discovered two group compounds isolated namely stigmasta-5,22-dien-3-β-ol (1) and stigmasta-5,22-dien-on (2), from n-hexane and chloroform extracts. The chemical structure of compounds 1 and 2 were identified based on IR spectroscopic, 1H NMR and 13C NMR and compared spectra data with data of compounds by other researchers. Compounds 1 and 2 are evaluated of their toxicity activity against shrimp larvae (Artemia salina) shows that the compound 1 shows weak toxicity activities against Artemia salina with LC50 value of 548.48 μg/mL, meanwhile the compound 2 exhibits a high inhibitory by LC50 value of 410.81 μg/mL. Based on this study, we suggest that the compound 2 has good bioactivity compared with compound 1.